FACT SHEET: INDOOR AIR POLLUTION ON AIRCRAFT (Tufts Archival Research Center, 2007)
ACVA Atlantic Fact Sheet on Indoor Air Pollution on Aircraft. Reports that airlines are increasingly using recycled air to save money, leading to poor air quality on board. Proposed that better ventilation systems would alleviate health problems. Includes diagrams of improved ventilation systems.